Protecting Olympic participants from Covid-19 - The urgent need for a risk-management approach - Sparrow, A. K.; Brosseau, L. M.; Harrison, R. J.; Osterholm, R. T. (New England Journal of Medicine, 2021)
In late July, approximately 11,000 athletes and 4000 athletic-support staff from more than 200 countries will gather for more than 2 weeks of competition at the Tokyo Olympics. One month later, another 5000 athletes and additional staff will attend the Paralympics. According to the International Olympic Committee (IOC) Tokyo 2020 playbooks,1 which are intended to protect both participants and the people of Japan from SARS-CoV-2 infection, Olympic athletes are instructed to supply their own face coverings, are encouraged (but not required) to be vaccinated against Covid-19, and will undergo testing at unspecified intervals after they arrive in Japan.